2006
DOI: 10.1186/1471-2458-6-227
|View full text |Cite
|
Sign up to set email alerts
|

The effect of socioeconomic status on three-year mortality after first-ever ischemic stroke in Nanjing, China

Abstract: BackgroundLow socioeconomic status (SES) is associated with increased mortality after stroke in developed countries. This study was performed to determine whether a similar association also exists in China.MethodsA total of 806 patients with first-ever ischemic stroke were enrolled in our study. From August 1999 to August 2005, the three-year all-cause mortality following the stroke was determined. Level of education, occupation, taxable income and housing space were used as indicators for SES. Stepwise univar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 24 publications
3
38
0
3
Order By: Relevance
“…7 Several studies have reported an association between SES and mortality after stroke based on different SES indicators but without controlling for differences in care. 6,9,10,12 In contrast, other studies reported no association between SES and stroke mortality when using SES indicators based on occupation or area-based deprivation indices. 3,5,13,14 We found no association between educational level and mortality, which confirms previous observations.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…7 Several studies have reported an association between SES and mortality after stroke based on different SES indicators but without controlling for differences in care. 6,9,10,12 In contrast, other studies reported no association between SES and stroke mortality when using SES indicators based on occupation or area-based deprivation indices. 3,5,13,14 We found no association between educational level and mortality, which confirms previous observations.…”
Section: Discussionmentioning
confidence: 92%
“…3,5,13,14 We found no association between educational level and mortality, which confirms previous observations. 4,9,10 A few studies have reported sex specific socioeconomicrelated differences in mortality. Jakovljevic et al found an association between low education and 28-day and 1-year case-fatality, which was limited to women aged 25 to 59 years.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] The reason why education itself was not associated with mortality in previous studies may be explained by shorter follow-up periods limited to 3 years 21,22 and considerably smaller numbers of patients. 22,34 We consider the effect of educational history to be effective in long-term follow-up modulating patient cooperation and compliance. The effect of different health care systems and overall socioeconomic status may prevent direct comparison of the results with previous ones.…”
Section: Strokementioning
confidence: 99%
“…The effect of different health care systems and overall socioeconomic status may prevent direct comparison of the results with previous ones. 34 Patients living alone were more often poorly educated. Because social support also is an important factor modifying stroke mortality, 13 we adjusted our analyses with marital status, therefore excluding the potential confounding effect.…”
Section: Strokementioning
confidence: 99%
“…Penelitian di China, pasien mengalami stroke pada usia < 50 tahun karena proporsi merokok dan konsumsi minuman beralkohol yang tinggi. 10 Kenaikan risiko serebro infark dan faktor risiko vaskuler pada umur dewasa muda terutama terjadi di negara berkembang berhubungan dengan peningkatan perilaku merokok dan urbanisasi. 11 Berdasarkan status ekonomi, responden yang miskin (kuintil 1 dan kuintil 2) berisiko lebih tinggi untuk mengalami stroke dibandingkan dengan status ekonomi yang lebih tinggi (tidak miskin).…”
Section: Hasilunclassified